2005
DOI: 10.2166/wst.2005.0043
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to experimental data of pollutant site mean concentration in stormwater runoff

Abstract: Urban wet weather discharges are known to be a great source of pollutants for receiving waters, which protection requires the estimation of long-term discharged pollutant loads. Pollutant loads can be estimated by multiplying a site mean concentration (SMC) by the total runoff volume during a given period of time. The estimation of the SMC value as a weighted mean value with event runoff volumes as weights is affected by uncertainties due to the variability of event mean concentrations and to the number of eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
2
13
0
3
Order By: Relevance
“…Even the simplest regression models have an additional calibration coefficient to SMC estimates, implying they will not perform well at sites with limited sampling, potentially overfitting on smaller datasets. This is supported by Mourad et al (2005aMourad et al ( , 2005bMourad et al ( , 2005c and Obropta and Kardos (2007) who suggested that SMCs required fewer data than regression or build-up washoff models. Furthermore, the study by May and Sivakumar (2013) found that the flow-weighted mean began performing less accurately on smaller datasets, potentially due to outlying storm event(s), which dominated the calibration of SMC.…”
Section: Authors' Replymentioning
confidence: 62%
See 2 more Smart Citations
“…Even the simplest regression models have an additional calibration coefficient to SMC estimates, implying they will not perform well at sites with limited sampling, potentially overfitting on smaller datasets. This is supported by Mourad et al (2005aMourad et al ( , 2005bMourad et al ( , 2005c and Obropta and Kardos (2007) who suggested that SMCs required fewer data than regression or build-up washoff models. Furthermore, the study by May and Sivakumar (2013) found that the flow-weighted mean began performing less accurately on smaller datasets, potentially due to outlying storm event(s), which dominated the calibration of SMC.…”
Section: Authors' Replymentioning
confidence: 62%
“…Regression and/or process-based models are not solely limited by the absence of strong correlations between concentration and explanatory variables such as discharge, but also by a sparsity of available stormwater quality data, due to economic factors preventing the sampling of multiple storm events at a single catchment (Brezonik and Stadelmann, 2002;Driver and Tasker, 1990;Mourad et al, 2005aMourad et al, , 2006Sliva and Williams, 2001). This sparsity of data makes it difficult to isolate typical trends accurately, supporting the use of simpler models such as SMC estimates.…”
Section: Authors' Replymentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used method to estimate the central EMC distribution value is the site mean concentration (SMC) computed as the arithmetic mean of the EMCs. However, the minimum number of EMCs and their statistical distribution are required to find a reliable SMC as a representative mean value (Mourad et al 2005).…”
Section: Data Analysesmentioning
confidence: 99%
“…REMC is a volume-weighted EMC mean for one specific site for different storm runoff volumes. This is a valid approach where a significant correlation exists between the EMC and runoff volume (Mourad et al 2005) and produces the most accurate long-term load estimates (May and Sivakumar 2012).…”
Section: Data Analysesmentioning
confidence: 99%